An experimental study on oxidative coupling of methane over Mn/Na2WO4/SiO2 catalyst - Düşova, Yeşim. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2014., 2014)
The oxidative coupling of methane (OCM) over Mn/Na2WO4/SiO2 catalyst was investigated in this work. The 2wt%Mn/5wt%Na2WO4/SiO2 catalysts were prepared using various methods (such as incipient to wetness impregnation, sol-gel and hydrothermal synthesis) and tested in a microflow quartz reactor for OCM process. Preliminary works were performed with 2wt.%Mn/5wt.%Na2WO4/SiO2 particulate catalyst wall coated on the FeCrAl alloy plate replaced in a metal micro-channel reactor; the results were not satisfactory due to the weak adhesion of the silica support on the metal plate. Then the catalyst was wash-coated on a cordierite monolithic support resulting a better performance. In addition, the other catalytic structures such as particulate fixed beds, whole-structural rods (monosil) and mesoporous silica network (MCM-41) were also prepared and tested under various operating conditions(such as reactor filling material, operation temperature and feed composition). The reactor outlet stream was analyzed using gas chromatography to determine the CH4 conversion and C2 hydrocarbon selectivity. The highest yield (14.2%) was obtained using the particulate catalyst prepared by incipient to wetness impregnation method. The decreasing inside diameter of reactor from 10 mm to 2 mm after the catalyst bed, and filling the empty space with quartz chips significantly improved the catalytic performance. The highest C2 yield was obtained at 650ºC with CH4/O2 ratio of 7.
Keywords: Methane -- Oxidation.